Neoteric Finance and Evolution in Banking Operation in India. - Ms. Kavisha Mineshkumar Shah; Dr. Arnaz Kaizad Wadia (Journal of Corporate Finance Management and Banking System, 2023)
The Sustainability of economic growth is the primary motive of all nations. The Transformation of hard cash to an e - wallet is a phenomenon. Today all money - related transactions are dine digitally to avoid the wastage of paper and increase the awareness of digital currency in the economically weaker parts of the world. The utilization of electronic money will lead to a faster , easier , and more reliable way of doing day - to - day transactions. All corporate companies and businesses are shifting from paper money to digital money. The purpose of this research paper is to substitute traditional banking practices with digital banking practices. The advancement in technology and the internet has changed banking services to a much faster, easier, and secure way of doing a money transaction. People can send and receive money at anytime and anywhere without doing any paperwork. Government can always keep an eye on all the big transactions as the digital world make all the thing much transparent. All the miscellaneous and tedious work of manually filling up the form to apply for every banking service is shifted online which makes the process of verification easy for the banks.